Pengaruh Tingkat Kepuasan Pengguna Alat Simonair Terhadap Minat Pengguna Dalam Memonitoring Kualitas Air - Dany Fadhilah; Hikmah Rahmah; Nur Aziezah; Walidatush Sholihah; Faldiena Marcelita (Jurnal Kendali Teknik dan Sains, 2024)
Improving water quality is an important issue that governments and society must address. His one way to improve water quality is to monitor it regularly. Monitoring tools that are easy to use and accessible to the public can be a solution to improving water quality. The aim of this research is to assess how user satisfaction with Simonair affects their inclination towards monitoring water quality. The methodology involves conducting a survey with respondents utilizing the Simonair tool, and the gathered data is subjected to analysis through a straightforward linear regression examination.Top of Form The results show that users' satisfaction with the Simonair tool has a significant positive impact on their interest in water quality monitoring. The higher the user satisfaction, the more interested the user will be in  water quality monitoring with Simonair. Drawing from the findings of this investigation, it is possible to infer that users' satisfaction with the Simonair tool is an important factor influencing users' interest in water quality monitoring. Therefore, efforts are needed to increase user satisfaction with the Simonair tool and increase user interest in  water quality monitoring using Simonair.